Lean Mass, Muscle Strength, and Muscle Quality in Retired Rugby Players: The UK Rugby Health Project - Entwistle, Ian; Francis, Peter; Lees, Matthew; Hume, Patria; Hind, Karen (International Journal of Sports Medicine, 2022)
Although athletes from sports such as rugby have greater lean mass and strength during their playing careers, little is known about these characteristics post-retirement. Therefore, this study investigated lean mass, strength, and muscle quality in retired elite and amateur rugby players and non-contact athletes. Retired elite male rugby players (n=42, 43.9±10.3 y; 101.1±13.4 kg; 1.82±0.09 m), amateur rugby players (n=46, 48.0±10.5 y; 98.9±16.6 kg; 1.79±0.07 m) and non-contact athletes (n=30, 51.3±12.5 y; 91.3±13.4 kg; 1.79±0.07 m) received one total body dual-energy X-ray absorptiometry assessment of appendicular lean mass (ALM) and ALM index (ALMI). Grip strength was measured, and muscle quality (grip strength/unit of arm lean mass) was calculated. Sarcopenia was identified as ALMI<7.23 kg/m2 and handgrip strength<37.2 kg. Total lean mass, ALM and grip strength were greater in the elite rugby compared to amateur rugby and non-contact groups (p<0.01). There were no significant differences in muscle quality or sarcopenia prevalence. Retired elite rugby players had greater lean mass and grip strength than amateur rugby and non-contact athletes, although muscle quality was similar. The greater lean mass and strength might reflect genetic influences or previous participation in a highly physical sport.
Keywords: former athletes; retirement; sport; ageing; muscle; strength; sarcopenia